2023
DOI: 10.1007/s00109-023-02374-9
|View full text |Cite
|
Sign up to set email alerts
|

Large extracellular vesicles derived from human regulatory macrophages (L-EVMreg) attenuate CD3/CD28-induced T-cell activation in vitro

Martin Albrecht,
Lars Hummitzsch,
Rene Rusch
et al.

Abstract: Macrophages belong to the innate immune system, and we have recently shown that in vitro differentiated human regulatory macrophages (Mreg) release large extracellular vesicles (L-EVMreg) with an average size of 7.5 μm which regulate wound healing and angiogenesis in vitro. The aim of this study was to investigate whether L-EVMreg also affect the CD3/CD28-mediated activation of T-cells. Mreg were differentiated using blood monocytes and L-EVMreg were isolated from culture supernatants by differential centrifug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Prior research conducted by the authors has been dedicated to characterizing Mreg for several years [ 8 , 12 , 16 ], demonstrating their ability to secrete pro-angiogenic factors, particularly under hypoxic conditions [ 8 ]. Building upon these findings, a GMP-compliant protocol for the production of Mreg was developed and a phase I/II study employing Mreg for treating patients with chronic limb threatening ischemia (CLTI) is under preparation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research conducted by the authors has been dedicated to characterizing Mreg for several years [ 8 , 12 , 16 ], demonstrating their ability to secrete pro-angiogenic factors, particularly under hypoxic conditions [ 8 ]. Building upon these findings, a GMP-compliant protocol for the production of Mreg was developed and a phase I/II study employing Mreg for treating patients with chronic limb threatening ischemia (CLTI) is under preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Different research groups have demonstrated in recent years that distinct macrophage subtypes can be differentiated in vitro by the administration of various cytokines/ factors (e.g., IL-4, IL-13, IFNγ, LPS), signifying the potential of these in vitro-differentiated cell types in the context of cell therapy [10,11]. We and others have shown that the administration of IFNγ on day 6 of the differentiation period can generate an anti-inflammatory, T-cell suppressive, and potentially pro-angiogenic macrophage subtype known as regulatory macrophages (Mreg) [7,8,[12][13][14][15]. These Mreg cells have already been successfully employed in a clinical study to reduce rejection reactions in kidney transplantations [4,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation